Functional consequences of the arrhythmogenic G306R KvLQT1 K(+) channel mutant probed by viral gene transfer in cardiomyocytes - Li, Ronald A (Blackwell Science Inc, 2001)
1. I(Ks), the slow component of the delayed rectifier potassium current, figures prominently in the repolarization of heart cells. The K(+) channel gene KvLQT1 is mutated in the heritable long QT (LQT) syndrome. Heterologous coexpression of KvLQT1 and the accessory protein minK yields an I(Ks)-like current. Nevertheless, the links between KvLQT1 and cardiac I(Ks) are largely inferential. 2. Since the LQT syndrome mutant KvLQT1-G306R suppresses channel activity when coexpressed with wild-type KvLQT1 in a heterologous system, overexpression of this mutant in cardiomyocytes should reduce or eliminate native I(Ks) if KvLQT1 is indeed the major molecular component of this current. To test this idea, we created the adenovirus AdRMGI-KvLQT1-G306R, which overexpresses KvLQT1-G306R channels. 3. In > 60 % of neonatal mouse myocytes, a sizable I(Ks) could be measured using perforated-patch recordings (8.0 ± 1.6 pA pF(−1), n = 13). I(Ks) was increased by forskolin and blocked by clofilium or indapamide but not by E-4031. While cells infected with a reporter virus expressing only green fluorescent protein (GFP) displayed I(Ks) similar to that in uninfected cells, AdRMGI-KvLQT1-G306R-infected cells showed a significantly reduced I(Ks) (2.4 ± 1.1 pA pF(−1), n = 10, P < 0.01) when measured 60-72 h after infection. Similar results were observed in adult guinea-pig myocytes (5.9 ± 1.2 pA pF(−1), n = 9, for control vs. 0.1 ± 0.1 pA pF(−1), n = 5, for AdRMGI-KvLQT1-G306R-infected cells). 4. We conclude that KvLQT1 is the major molecular component of I(Ks). Our results further establish a dominant-negative mechanism for the G306R LQT syndrome mutation.